INVESTIGATION OF NONISOTHERMAL MOTION OF DROSS BERYLLIUM OXIDE IN ROUND DRAW - Zhapbasbayev U.К.; Sattinova, Z.K. (Recent Contributions to Physics, 2018)
The results of investigations of nonisothermal motion of thermoplastic dross of beryllium oxide in round draw plate are presented. Velocity and temperature fields with taking into account dross mass crystallization are received. Laws of change of thermal flow density and Nusselt criterion depending on regime parameters are defined.